The impact of the reaction to diagnosis on sibling relationship: a study on parents and adult siblings of people with disabilities - Lecciso, Flavia; Martis, Chiara; Antonioli, Giuseppe; Levante, Annalisa (Frontiers in Psychology, 2025)
ObjectiveBuilding on Bowlby's attachment theory and Marvin and Pianta's framework, the current study investigated the role of the resolution of the diagnosis as a potential protective factor in shaping the quality of affective sibling relationships. The study examined whether the typically developing (TD) siblings' resolution of the diagnosis of their brother/sister with a disability would predict the quality of their affective relationship in terms of closeness, conflict, jealousy, self-marginalization, and worry (HP1). The potential predictive role of parental resolution on typically developing sibling resolution has been investigated (HP2). In addition, we explored whether being an older vs. younger typically developing sibling would impact the resolution of the diagnosis and the quality of the affective sibling relationship.MethodsA total of 365 parent–sibling dyads [parents: Mage(SD) = 51.2 (6.95) years, age range = 25–64 years; mothers = 78.4%; TD siblings: Mage(SD) = 23.2 (3.60) years, age range = 18–39 years; females = 53.7%] from families of individuals with neurodevelopmental disorders or physical disabilities filled out the e-survey (CE n° 92,949/2,023).ResultsThe results supported both hypotheses, highlighting the potential protective role of typically developing siblings' resolution of the diagnosis in fostering high-quality sibling relationships in terms of high closeness and low conflict, jealousy, self-marginalization, and worry. In addition, parental resolution of the diagnosis emerged as a potential predictor of typically developing siblings' resolution, supporting the intergenerational transmission of internal working models. Regarding the research question (RQ), younger typically developing siblings reported higher resolution scores than their older counterparts, suggesting that typically developing sibling birth order may shape the reaction to the diagnosis process.ConclusionThe results underscored the importance of systemic interventions that devote attention not only to parental resolution but also to that of typically developing siblings. Future research should deepen the role played by socio-demographic factors and long-term outcomes on typically developing siblings' mental health and caregiving duties.